Focal masses in a non-cirrhotic liver: The additional benefit of CEUS over baseline imaging. Issue 9 (September 2015) - Chiorean, L.; Cantisani, V.; Jenssen, C.; Sidhu, P.S.; Baum, U.; Dietrich, C.F.
Highlights: Contrast-enhanced ultrasound in detection of focal liver lesions. Contrast-enhanced ultrasound in characterization of focal liver lesions. Contrast-enhanced ultrasound in differential diagnosis of focal liver lesions. Contrast-enhanced ultrasound in final diagnosis of focal liver lesions. Contrast-enhanced ultrasound in liver metastases screening. Roles of cross-sectional imaging techniques for focal liver lesions assessment. Advantages of contrast-enhanced ultrasound over other imaging procedures. Abstract: Incidentally detected focal liver lesions are commonly encountered in clinical practice presenting a challenge in the daily department work flow. Guidelines for the management of incidental focal liver lesions have been published but comments, illustrations and recommendations regarding practical issues are crucial. The unique features of contrast-enhanced ultrasound in non-invasive assessment of focal liver lesion enhancement throughout the vascular phases in real-time has allowed an impressive improvement in the diagnostic accuracy of ultrasound. We highlight the additional benefit of contrast-enhanced ultrasound over conventional B-mode ultrasound imaging in detection, characterization, differential and final diagnosis of focal liver lesions, as well as for liver metastases screening. The current roles of cross-sectional imaging are explained in detail, with indications and limitations for each procedure. The advantages of CEUS, such as non-ionizing radiation exposure, cost benefits, non-iodinate contrast agents, and repeatability are also described ultimately improving patient management.